Spermiogenesis and introsperm ultrastructure of Scoloplax distolothrix (Ostariophysi : Siluriformes : Scoloplacidae) - Spadella, Maria Angelica; Oliveira, Claudio; Quagio-Grassiotto, Irani (Wiley-Blackwell, 2006)
Spermiogenesis in scoloplacids is characterized by initial lateral development of the flagellum, nuclear rotation, medial nuclear fossa formation, complex centriolar migration, and cytoplasmic channel formation. The scoloplacid spermiogenesis is similar to those found in Diplomystidae, the most primitive siluriform family. The scoloplacid spermatozoa have all the main characteristics of introsperm. They exhibit a conic head, a symmetric midpiece, a medial flagellum, and no acrosome. The conic forward-elongated nuclei contain homogeneous chromatin. The thin extremity of the nuclei is strongly curved and along its internal face there is a well-developed membranous compartment. The centrioles are completely inside the medial nuclear fossa, perpendicular to each other and with an electron-dense material between them. In a cross view of the midpiece, the mitochondria form a ring surrounding internally the cytoplasmic channel, and in a longitudinal view they are organized in a row along it. Several elongated vesicles are distributed peripherally, mainly concentrated in the mid-piece basal region. The flagellum contains the classical axoneme (9 + 2) and has two lateral projections or fins. The spermatozoa of scoloplacids share several characteristics with those of Auchenipteridae. Since these two families are not phylogenetically related this similarity seems to be due to convergence once both families are, until now, the only known siluriform families with introsperm.
Keywords: catfish; evolution; germinative cells; spermatozoa; ultrastructure